2020
DOI: 10.1002/jdd.12183
|View full text |Cite
|
Sign up to set email alerts
|

Fink's integrated course design and taxonomy: The impact of their use in a “Basics of Dental Anatomy” course

Abstract: Objective This study aimed to assess whether the adjustment of Fink's Model of Integrated Course Design (ICD) with his Taxonomy of Significant Learning (hereinafter referred to as “ICD/SL”) affected the academic performance of students at Universidad El Bosque in the “Basics of Dental Anatomy” course. Design For this purpose, 3 academic groups were selected: 2018/1 (55 students), 2018/2 (79 students), and 2019/1 (57 students). The control group, 2018/1, was taught without ICD/SL; the 2 treatment groups, 2018/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As a result, teachers have no exposure to other taxonomies such as Fink's Taxonomy. However, for teachers who are familiar with Fink's Taxonomy, issues arise when the teachers are less skilled and do not master the elements of Fink's Taxonomy (Uribe Cantalejo & Pardo, 2020). This issue began to be highlighted in recent years when more and more academics began to criticize the shortcomings of Bloom's Taxonomy (Berger, 2018;Lemov, 2017) and attempt to look at other taxonomies.…”
Section: Issues and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, teachers have no exposure to other taxonomies such as Fink's Taxonomy. However, for teachers who are familiar with Fink's Taxonomy, issues arise when the teachers are less skilled and do not master the elements of Fink's Taxonomy (Uribe Cantalejo & Pardo, 2020). This issue began to be highlighted in recent years when more and more academics began to criticize the shortcomings of Bloom's Taxonomy (Berger, 2018;Lemov, 2017) and attempt to look at other taxonomies.…”
Section: Issues and Discussionmentioning
confidence: 99%
“…Studies related to Fink's Taxonomy have been conducted abroad since it was introduced by L. Dee Fink in 2003. There are many recent studies on Fink's Taxonomy (Su, 2022;DeLuca et al, 2021;Mandur et al, 2021;Mukdaprasert & Chalauisaeng, 2021;Barton 2020;Partido et al, 2020;Faisal 2020;Billiot & Forbes 2020;Uribe & Pardo 2020;Branzetti et al 2019;Keating et al 2019;Pampel 2018;Odom et al, 2017); however, recent studies on Fink's Taxonomy in Malaysia are very limited. Faisal (2020) conducted a study of Fink's Taxonomy in the context of Science in Pakistan and evidenced that most students demonstrated poor Science competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fink's taxonomy relevance to professional education has been documented in various fields of health professions education (Branzetti et al, 2019; Partido et al, 2020; Uribe Cantalejo & Pardo, 2020). It has immediate relevance to medical education as reported for the tenets of foundational knowledge and application, which are particularly relevant to competency‐based training where the themes could be used by educators to create improved learning experiences for trainees (Branzetti et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fink's Taxonomy and ICD have been shown to result in improved student outcomes and learning, when intentionally incorporated into a basic dental anatomy course (Uribe Cantalejo & Pardo, 2020), and positively impacted student learning in a dental hygiene course (Partido et al, 2020). In these studies, students reported a positive focus on foundational knowledge, active learning, and positive influence on student learning (Partido et al, 2020; Uribe Cantalejo & Pardo, 2020). Fink's Taxonomy is relevant to the earlier stages of medical education and training as well, specifically when one considers the tenets of caring and human dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation